PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA PADA MATA PELAJARAN IPA - Mahbubah; Ririn Andriani Kumala Dewi; Dadang Suhada (STKIP Subang, 2025)
The lack of innovation in learning models in class IV science (Natural Sciences) learning at UPTD SDN 6 Dadap, which has resulted in low learning outcomes and student activity, is the background for carrying out this research. One solution that can be carried out is by implementing contextual learning models. This research aims to determine the application of the Contextual Teaching and Learning model, to determine the increase in science learning outcomes regarding plant parts and their functions for class IV UPTD SD Negeri 6 Dadap students by implementing the Contextual Teaching and Learning learning model. This research is Classroom Action Research using the Kemmis and MC models. Tagget, implemented in 3 cycles, each cycle consisting of 4 stages, planning, action, observation and reflection. The population in this study were all UPTD students at SDN 6 Dadap, with a sample of 20 students. Data is collected through tests and observations. The research results show that the contextual model can significantly improve learning outcomes and student activity. It can be seen that in cycle I it shows the poor category by getting a score of 25%, in cycle II it shows the adequate category by getting 65% and in cycle III it shows the very good category by getting a score of 90%. Meanwhile, student activity in cycle I was 50.37%, which was in the poor category, increased in cycle II to 58.25%, which was in the sufficient category, and continued to increase in cycle III, as much as 66%, which was in the good category.